Upaya Pencegahan Stunting Berbasis Edukasi dan Sosialisasi - Rasi Rahagia; Sriyanah, Nour; Aris Tyarini, Indrawati; Lontaan, Anita; Yunus, Muh (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Health problems should be particularly noted from infancy. The problem that occurs a lot in Indonesia today is stunting. Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, resulting in growth disorders in children, namely lower or shorter child height. This activity aims to increase stunting prevention efforts based on education and socialization. The implementation method used in this activity is the follow-up review method with a participatory action program approach involving posyandu cadres. The results of observations in this activity were that active children followed the steps of washing their hands. Conclusion. Service activities were carried out well, and there was an increase in maternal knowledge about stunting prevention. The advice from this activity is for the community to actively obtain information about stunting prevention and the active role of cadres in educating the community about stunting in each posyandu activity.